Ibadah Intergenerasi dan Motivasi Beribadah Di Tengah Tantangan Bergereja Secara Individualistik Dan Konsumeristik - Kukuh Purwidhianto (Institut Agama Kristen Negeri Toraja, 2022)
This article wants to show that intergenerational worship is not just a technical matter of combining all generations into one worship. Moreover, intergenerational worship contains a depth of biblical, theological, philosophical values ​​and has a function as a space to process and learn about Christian values ​​(understanding). Through intergenerational worship, church members from all generations learn (process) to build the right motivation in worship. The main thing is not about receiving but giving, even giving the best for God. Intergenerational worship emphasizes the collectivity, not personality. Not just competing to pursue desires (consumptive) and satisfaction (individualistic) themselves and generation groups, on the contrary, it encourages each generation to be more open, humble and willing to learn from each other. Intergenerational worship is also a learning space to reconcile tensions, erode competition (competition) and the tendency to dominate between generations. Abstrak: Artikel ini ingin menunjukkan bahwa ibadah intergenerasi bukan sekadar persoalan teknis menggabungkan seluruh generasi ke dalam satu ibadah. Lebih dari itu ibadah intergenerasi mengandung kedalaman nilai-nilai biblis, teologis, filosofis dan memiliki fungsi sebagai ruang berproses dan belajar tentang nilai-nilai (pemahaman) kristiani. Melalui ibadah intergenerasi, warga gereja dari semua generasi belajar (berproses) membangun motivasi yang tepat dalam beribadah. Yang utama bukan tentang menerima melainkan memberi, bahkan memberi yang terbaik untuk Tuhan. Ibadah intergenerasi menitiktekankan pada aspek kolektivitas bukan personalitas. Bukan sekadar berlomba-lomba mengejar keinginan (konsumtif) dan kepuasan (individualistik) diri serta kelompok generasi, sebaliknya mendorong setiap generasi makin terbuka, rendah hati dan mau saling belajar satu sama lain. Ibadah intergenerasi juga menjadi ruang belajar medamaikan ketegangan, mengikis persaingan (kompetisi) maupun kecenderungan mendominasi antar generasi satu terhadap yang lain.